Zahtevnost rehabilitacije bolnišničnih pacientov na Inštitutu za rehabilitacijo v letih 2001 do 2007 - Puzić Ravnjak, Nataša (Rehabilitacija (Ljubljana), 2009)
Background: Rehabilitation team members at the Institute for Rehabilitation have noticed that in the recent years diseases and problems of inpatients have become more severe and complex. At the same time, the physicians have noticed an increase in the number of required interventions and complications that have been addressed when on duty. The aim of the study was to objectively confirm those observations. Methods: Data analysis was based on 360 randomly selected medical records (5 patients admitted to each of the six departments at the Institute in February, March, September and October in 2001, 2004 and 2007) and the "doctor on duty register" where complications and interventions are entered (from September to November in 2004 and 2007). The number of diagnoses at the admission was checked as well as all individual and the total number of complications and interventions during inpatient rehabilitation. Results: The average number of diagnoses increased in 2004 and 2007 compared to 2001. The number of complications per patient was higher in 2004 and 2007 than in 2001. The increase was noticed in all the departments at the Institute. The highest number of complications was observed at the Department for rehabilitation of patients with spinal cord lesions and the lowest at the Department for (re)habilitation of children. The most frequent complication was urinary tract infection. The frequency of severe complications and demanding interventions increased. Conclusions: In the period from 2001 to 2007 the exigency of medical cases increased. Complications and interventions have become more demanding in the recent years.
Keywords: rehabilitacija; vocational rehabilitation; težavnost; zapleti; posegi